2016
DOI: 10.2514/1.t4488
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Friction in a Square Channel with Ribs and Grooves

Abstract: Turbulence promoters have been widely applied to enhance heat transfer in internal flow channels, although they cause pressure loss. This study employed the transient liquid-crystal technique to measure the heat transfer distribution in a square channel with compound turbulence promoters with orthogonal (90 deg), continuous angled (45 deg), discrete angled (45 deg), V-shaped, and inverted-V-shaped rib configurations. The rib height-to-hydraulic diameter ratio (e∕D h ) and the rib pitch-to-height ratio (P∕e) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The average Nusselt numbers from the air flow are plotted against the Reynolds numbers in Figure 11a, and the results are comparable with those obtained from the literature data [22]. The Nu values from the smooth case were compared to the Sieder-Tate correlation:…”
Section: Average Nusselt Number and Friction Factorsupporting
confidence: 66%
“…The average Nusselt numbers from the air flow are plotted against the Reynolds numbers in Figure 11a, and the results are comparable with those obtained from the literature data [22]. The Nu values from the smooth case were compared to the Sieder-Tate correlation:…”
Section: Average Nusselt Number and Friction Factorsupporting
confidence: 66%
“…Moreover, the V-shaped and discrete V-shaped ribs were also the most effective design for heat transfer enhancement in the rotating triangular cooling channels [13]. The performance of the V-shaped ribs could be further improved, such as by adding the grooves between the ribs [14]. In addition to the air flow, the broken V-shaped ribs were also effective for raising the air-water mist cooling effect [15].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the heat transfer performance, many researches on the combination of different protrusions and grooves have been determined [20][21][22][23][24][25]. Jaurker et al [20] compared the thermal performance between the ribbed channel and the rib-grooved channel, and they found that the rib-grooved channel performed better than the stand-alone ribbed channel.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Saha et al [22] pointed out that a channel using the combination of angled grooves with angled ribs exhibited the best thermal performance, compared with the channels using angled grooves with different pitches or the combinations of angled grooves with transverse ribs. Besides, Liu et al [23] measured the heat transfer distribution in a channel with rib-grooves of orthogonal, continuous angled, discrete angled, V-shaped, inverted-V-shaped configurations, and they found that the discrete angled rib-grooves could obtain the maximal heat transfer enhancement and thermal performance. Skullong et al [24] experimentally investigated the effect of combined wavy grooves and trapezoidal-winglets on the flow and heat transfer characteristics in a solar air heater channel, and their results showed that the combined turbulators performed better than the stand-alone devices.…”
Section: Introductionmentioning
confidence: 99%